마케팅환경 변화에 따른 통합커뮤니케이션디자인 전략 - 양재범(Jae-Bum Yang) (한국콘텐츠학회 논문지, 8(5), 2008)
Researcher tried to argue the possibility of application of visual communication design adapting the marketing environment change on this paper. What is ICD (Integrated Communication Design)? This is a new attempt to treat these common marketing methods, such as, C, I, B, I, TV commercials, newspaper commercials, posters, brochures, DM, package designing, POP, outdoor visual information, web sites etc, as a whole. And no longer treat them as separate pieces as we were doing previously. So I started this research with positive analysis which already has been theoretically discussed based on the documents and researches on the same subject. Through this attempt I tried to examine the possibility of application of ICD. Conclusively, I developed and suggest named the ICD model, by which we could explain the current marketing communication design effort more holistically then ever. 본 논문은 마케팅 환경 변화에 따른 통합 커뮤니케이션디자인의 적용 가능성을 연구하고자 하였다. 통합커뮤니케이션디자인이란(ICD : Integrated Communication Design)? 종전의 판매촉진 수단으로써 특히 가장 일반적인 형태인 CI, BI, TV광고, 신문광고, 포스터, 브로슈어, DM, 패키지디자인, POP, 옥외 시각 정보 물, 홈페이지 등을 개별적으로 보았던 것을 전체적으로 확대해서 소비자 관점에서의 정보처리 시각으로 파악하려는 커뮤니케이션디자인의 새로운 시도이다. 따라서 본 연구에서는 통합 커뮤니케이션 디자인의 실증적 분석을 위해 먼저 마케팅 환경 변화의 기존 자료 및 문헌을 바탕으로 한 이론적 논의를 하였다. 또한 ICD를 제안하면서 시각디자인 각 분야 간의 벽을 헐고 디자인 과업을 가치 지향적으로 통합하여 수행하는 통합커뮤니케이션디자인의 개념과 전략, 그리고 실천 방향에 대한 의견을 제시하였다.